Physics Concepts Analysis in the Traditional Games of Kekehan - Deta, Utama Alan; Arisanti, Aini; Hudha, Muhammad Nur; Lestari, Nurita Apridiana; Admoko, Setyo; Uulaa, Rizki Fitri Rahima; Prahani, Binar Kurnia; Suprapto, Nadi (International Journal of Research and Community Empowerment, 2024)
Indonesia has an enormous amount of diversity, and unconsciously every culture has a different attraction. In its own culture, there is a science of physics that few people know much about, but local wisdom from several different areas can be used as a source of study in physics, one of which is traditional kekehan games. The study aims to understand the concept of physics in the traditional games of kekehan. The research method used in this study is qualitative descriptive methods. The approach used in this study is the ethnographic approach. The data collection method used is observation, documentation, and literature study. Observation and documentation are done in the physics education program at surabaya state university. From observation, documenting and literature studies, it can be concluded that mass influences the acceleration of the hostility Angle, where it inverse to angular acceleration. The second experiment showed that the fingers affect the rotation time. And it can also be discovered that the square of the finger is comparable to the kinetic energy rotation. The concept of physics of inertia includes moments of inertia, angles, heavy forces, circular motion, torque, and style moments.